Small extracellular vesicles derived from four dimensional-culture of mesenchymal stem cells induce alternatively activated macrophages by upregulating IGFBP2/EGFR to attenuate inflammation in the spinal cord injury of rats - Wang, Junhua; Wei, Qingshuai; Yang, Yue; Che, Mingtian; Ma, Yuanhuan; Peng, Lizhi; Yu, Haiyang; Shi, Huijuan; He, Guanheng; Wu, Rongjie; Zeng, Ting; Zeng, Xiang; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Effectively reducing the inflammatory response after spinal cord injury (SCI) is a chal-lenging clinical problem and the subject of active investigation. This study employed a porous scaffold-based three dimensional long-term culture technique to obtain human umbilical cord mesenchymal stem cell (hUC-MSC)-derived Small Extracellular Vesicles (sEVs) (three dimensional culture over time, the “4D-sEVs”). Moreover, the vesicle size, number, and inner protein con-centrations of the MSC 4D-sEVs contained altered protein profiles compared with those derived from 2D culture conditions. A proteomics analysis suggested broad changes, especially significant upregulation of Epidermal Growth Factors Receptor (EGFR) and Insulin-like Growth Factor Binding Protein 2 (IGFBP2) in 4D-sEVs compared with 2D-sEVs. The endocytosis of 4D-sEVs al-lowed for the binding of EGFR and IGFBP2, leading to downstream STAT3 phosphorylation and IL-10 secretion and effective induction of macrophages/microglia polarization from the pro-inflammatory M1 to anti-inflammatory M2 phenotype, both in vitro and in the injured areas of rats with compressive/contusive SCI. The reduction in neuroinflammation after 4D-sEVs delivery to the injury site epicenter led to significant neuroprotection, as evidenced by the number of surviving spinal neurons. Therefore, applying this novel 4D culture-derived Small Extracellular Vesicles could effectively curb the inflammatory response and increase tissue repair after SCI.